2021
DOI: 10.3390/jrfm14020063
|View full text |Cite
|
Sign up to set email alerts
|

Granger Causal Nexus between Good Public Governance and Unemployment: Evidence from Cross-Country Panel Data Investigation

Abstract: The purpose of this paper is to investigate the causality between good public governance captured through six World Bank governance indicators and unemployment rate (unemployment as % of the total labour force) as a clear indicator of labour market performance. Although some previous papers have empirically demonstrated the casual nexus between country-level governance and economic development, this study investigates the relation of causality between public governance and the labour market. By employing Grang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The study further showed that extremely high youth unemployment rate, coupled with high incidences of corruption and inequalities, expose countries to national insecurity and political instability. Similarly, Bota-Avram et al (2021) evaluated the causal relationship between public governance and labour market performance and the finding revealed bidirectional causality between unemployment and public governance across the selected countries.…”
Section: Institutions/governance and Unemploymentmentioning
confidence: 99%
“…The study further showed that extremely high youth unemployment rate, coupled with high incidences of corruption and inequalities, expose countries to national insecurity and political instability. Similarly, Bota-Avram et al (2021) evaluated the causal relationship between public governance and labour market performance and the finding revealed bidirectional causality between unemployment and public governance across the selected countries.…”
Section: Institutions/governance and Unemploymentmentioning
confidence: 99%